Profile of Head Injury Cases Reported in Western India: An Autopsy Study - Reena A. Jain; Madhusudan R. Petkar; Shweta Patel; Ashwinikumar B. Sapate; Vikrant Kalokhe (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: Head injuries, especially those resulting fromroad traf𿿿c accidents (RTAs), are a signi𿿿cant public health concern in India, particularly amongtheyoung population. This autopsy-based study aimed to evaluate the demographic pro𿿿le, causative factors, survival times, and the pattern of skull fractures infatal head injury cases reported in a tertiary care hospital in Western India. Results: A total of 350 autopsied cases of fatal head injuries were analyzedover one year. The majority were males (84.29%), with the most affected age group being 21–30 years (24%). Accidental head injuries accounted for 90.57% of cases, and RTAs were the leading cause (67.14%). Two-wheeler occupants represented the most common victim group, with 82% of them not wearing helmets. Headon collisions were the most frequent RTA type. Most deaths (over 60%) occurred within 12 hours of injury. Skull base and vault fractures were signi𿿿cantlymorecommon among non-helmeted riders. Discussion: The𿿿ndings indicate a strong association between lack of helmet use nd fatal skull fractures. Young adult males are at greater risk due to increased xposure to outdoor and vehicular activities. Delays in emergency response and limited trauma care infrastructure contribute to early mortality following head injury.